Paradoxes of Technology: Consumer Cognizance, Emotions, and Coping Strategies - Mick, David Glen; Fournier, Susan (Journal of Consumer Research, 1998)
Abstract Although technological products are unavoidable in contemporary life, studies focusing on them in the consumer behavior field have been few and narrow. In this article, we investigate consumers' perspectives, meanings, and experiences in relation to a range of technological products, emphasizing lengthy and repeated interviews with 29 households, including a set of first-time owners. We draw on literatures spanning from technology, paradox, and postmodernism to clinical and social psychology, and combine them with data collection and analysis in the spirit of grounded theory. The outcome is a new conceptual framework on the paradoxes of technological products and their influences on emotional reactions and behavioral coping strategies. We discuss the findings in terms of implications for theories of technology, innovation diffusion, and human coping, and an expanded role for the paradox construct in consumer research.